Portable water quality monitoring system for aquaponics using We MOS - Mohd Pu'ad, Muhamad Farhan; Sidek, Khairul Azami; Mel, Maizirwan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Technology today had advanced rapidly for the betterment of our life. However, agriculture seems to be left behind in the rapid progress. With the growing population nationwide, more food is required especially in the agriculture sector. Aquaponics is an efficient approach for food production which combines plant and fish farming together. In aquaponics, water quality especially the water’s pH level is crucial to be monitored regularly to ensure the fishes are in good health. However, measuring the pH level routine is no longer efficient today since the availability of technology. This study proposed a portable water quality monitoring system which currently only measures the water’s pH level since it is the most important parameter in water quality. Mainly, the system uses WeMos board and Message Queuing Telemetry Transport (MQTT) protocol for data processing and sending it to a Raspberry Pi (base station) for storage and visualisation. The device has been successfully tested at the Malaysian Institute of Sustainable Agriculture (MISA). website. The device was proven waterproof and floatable. It also can run for about 89 hours on battery only without solar panel. However, there is always area for improvement which includes adding more sensors to optimise usage of the device and also a Liquid-Crystal Display (LCD) screen for user convenience. Nonetheless, this is a step towards modernising the agriculture sector.